Hispanic/Latinx Ethnic Subgroup Differences in Sociodemographic, Sociocultural, and Smoking Characteristics in a Cessation Trial: An Exploratory Study. Issue 10 (2nd April 2022) - Medina-Ramirez, Patricia; Casas, Laura; Sutton, Steven K; Calixte-Civil, Patricia; Brandon, Karen O; Martinez, Ursula; Meade, Cathy D; Byrne, Margaret M; Brandon, Thomas H; Simmons, Vani N
Abstract: Introduction: Hispanic/Latinx smokers in the United States are often treated as a homogeneous group. However, population-based studies suggest that cigarette use differs among Hispanic/Latinx subgroups by sociodemographic or sociocultural characteristics. This secondary analysis aimed to advance the limited literature by examining differences in smoking-related variables. Aims and Methods: We used baseline data from a randomized controlled trial testing a self-help Spanish-language smoking cessation intervention. Puerto Rican (PR), Mexican, and Cuban, the three largest Hispanic/Latinx subgroups in the sample ( N = 1028), were first compared on sociodemographic and sociocultural variables (acculturation and familism). Primary analyses assessed subgroup differences in cigarette use variables (eg, cigarettes per day [CPD], nicotine dependence [Fagerström Test for Nicotine Dependence], and daily smoking) and smoking-related cognitive constructs (motivation to quit, smoking outcome expectancies, and abstinence self-efficacy) controlling for sociodemographic and sociocultural variables. Additional analyses explored differences between men and women within subgroups. Results: Mexicans exhibited the lowest levels of daily smoking (90% vs. 95% Cubans and 96% PR; p = .001), CPD (M = 13.5, SD = 9.5 vs. M = 20.1, SD = 9.9 Cubans and M = 16.7, SD = 10.1 PR; p = .016), and nicotine dependence (M = 4.2, SD = 2.3 vs. M = 6.0, SD = 2.1 Cubans and M = 5.7, SD = 2.2 PR; p < .001), with no differences between PRs and Cubans. Within-subgroup comparisons between men and women showed the most differences among PRs (eg, men were more nicotine dependent [M = 6.0, SD = 1.9] than women [M = 5.4, SD = 2.3; p = .041]) and Cubans (eg, men smoked more CPD [M = 22.2, SD = 12.2] than women [M = 19.3, SD = 12.0; p = .042]), and the fewest among Mexicans. Conclusions: Findings support heterogeneity within Hispanic/Latinx smokers and highlight the potential utility of examining sociodemographic, sociocultural, and smoking characteristics important for developing salient cessation interventions. Implications: Findings demonstrate that treatment-seeking Hispanic/Latinx smokers in the United States differ in sociodemographic, sociocultural, and smoking-related variables (cigarette use and smoking-related cognitive constructs) by subgroup (ie, PR, Mexican, and Cuban) and within subgroups by sex. These differences suggest that heterogeneity among subgroups should be considered when developing cessation interventions for Hispanics/Latinxs. Future research should examine how differences in sociodemographic and smoking-related variables impact intervention outcomes and explore the role of sociocultural factors (eg, acculturation and familism) as determinants of cessation.